THE EXTENT OF UNDERSTANDING AND IMPLEMENTATION OF DISASTER RISK MANAGEMENT PROGRAMS OF SAN MARIANO NATIONAL HIGH SCHOOL - Tarun, Jessabel Dumelod (Studies in Technology and Education, 2024)
This study aimed to determine the extent of understanding and implementing disaster risk management at San Mariano National High School. The Participatory School Disaster Management Toolkit, created by Save the Children as a contribution to the implementation of Comprehensive School Safety Pillar 2—School Disaster Management—was the data source for quantitative research, which employed the descriptive-evaluative method. The San Mariano National High School's understanding and implementation of disaster risk management were examined using the mean and standard deviation. A Likert scale was employed to gauge the level of understanding and implementation. Considering the results, although the faculty and staff of San Mariano National High School do not belong to the disaster risk reduction management council, programs and activities for disaster risk reduction are executed successfully. The results also showed that faculty and staff understand and participate in disaster risk reduction, response, and preparedness. However, many faculty members and staff encountered difficulties putting these programs into practice, so they were advised to develop a more comprehensive disaster risk reduction management plan that would meet the needs of the school, maintain and upgrade DRR programs, add more members to the DRR organization, purchase and identify facilities and equipment for emergencies, and finally regularly review and assess the implementation of disaster risk reduction programs to achieve very well-implemented DRRM programs.